2020
DOI: 10.1038/s41598-020-60630-1
|View full text |Cite
|
Sign up to set email alerts
|

Uptake routes of microplastics in fishes: practical and theoretical approaches to test existing theories

Abstract: Microplastics are frequently detected in the gastrointestinal tracts of aquatic organisms worldwide. A number of active and passive pathways have been suggested for fish, including the confusion of microplastic particles with prey, accidental uptake while foraging and transfer through the food chain, but a holistic understanding of influencing factors is still lacking. The aim of the study was to investigate frequently suggested theories and identify relevant biotic factors, as well as certain plastic properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(126 citation statements)
references
References 53 publications
(65 reference statements)
4
91
1
4
Order By: Relevance
“…Under environmentally relevant concentrations, where concentrations in the gastrointestinal tract are not at steady state with the external environment, and where the rate of passage through the gastrointestinal tract may be greater than the rate of biological uptake, accumulation within the organism is unlikely. Alternatively, when the gastrointestinal tract residence time is relatively long compared with the rate of biological uptake, then an increased probability for translocation may be possible (such as observed in the theoretical MICROWEB model applied to seals by Diepens and Koelmans [2018] and to fish by Roch et al [2020]). It is thus recommended that future studies should include efforts aimed at estimating gastrointestinal tract residence times for the species under investigation; such studies should also aim to characterize potential differences between species with different feeding strategies (i.e., filter‐feeders vs nonfilter‐feeders).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under environmentally relevant concentrations, where concentrations in the gastrointestinal tract are not at steady state with the external environment, and where the rate of passage through the gastrointestinal tract may be greater than the rate of biological uptake, accumulation within the organism is unlikely. Alternatively, when the gastrointestinal tract residence time is relatively long compared with the rate of biological uptake, then an increased probability for translocation may be possible (such as observed in the theoretical MICROWEB model applied to seals by Diepens and Koelmans [2018] and to fish by Roch et al [2020]). It is thus recommended that future studies should include efforts aimed at estimating gastrointestinal tract residence times for the species under investigation; such studies should also aim to characterize potential differences between species with different feeding strategies (i.e., filter‐feeders vs nonfilter‐feeders).…”
Section: Resultsmentioning
confidence: 99%
“…The interaction between organisms and particulates such as ENMs and microplastic particles is thus dynamic, not steady state, and the processes for uptake and elimination are driven by various endocytosis‐related mechanisms (Felix et al 2017), not by passive diffusion through tissues or via solute transporters as they are for soluble chemicals (Schultz 1976; DeVito 2000). Consequently, the assessment of poorly soluble particulates with respect to their potential to bioaccumulate may require the development of new test systems, models, and mechanistic understanding (Handy et al 2018; European Centre for Ecotoxicology and Toxicology of Chemicals 2019; Petersen et al 2019; Roch et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although MP encounter by fish is assumed to occur mainly during active feeding, there is increasing evidence of MPs being encountered via the gills and/or epidermis of wild freshwater fish (Abbasi et al, 2018;Hurt et al, 2020;Park et al, 2020). Experimental studies have also demonstrated MP accumulation on the gills (Mak et al, 2019;Roch et al, 2020). Passive uptake of MPs is thus an additional source of MPs following environmental exposure during swimming and respiration.…”
Section: Mp Encounter Rates In Freshwater Fishesmentioning
confidence: 99%
“…Microplastics include fragments, beads, films, and fibres smaller than 5 mm, which are introduced directly into the environment or are produced by weathering from larger plastic waste (Barnes et al., 2009; Lambert et al., 2014). In fish, there are several routes by which MPs might be ingested: they may be transferred directly through the food chain (Santana et al., 2017); accidentally ingested while eating or drinking (Roch et al., 2020); or in some cases, can be confused with food, leading to active ingestion (Ory et al., 2017).…”
Section: Introductionmentioning
confidence: 99%